2011
DOI: 10.1097/bcr.0b013e31820aade7
|View full text |Cite
|
Sign up to set email alerts
|

Severe Burn Injuries Caused by Bioethanol-Design Fireplaces—An Overview on Recreational Fire Threats

Abstract: Commercially available bioethanol-fueled fireplaces have become increasingly popular additions for interior home decoration in Europe and more recently in the United States. These fireplaces are advertised as smokeless, ecologically friendly, and do not require professional installation, formal gas lines, or venting. Although manufacturers and businesses promote their safety, recent presentations of injuries have alerted the authors to the relevant danger bioethanol fireplaces can pose for the incautious user.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 11 publications
0
10
0
Order By: Relevance
“…Recently, bioethanol-design fireplaces have been gaining in popularity because they do not need to be connected to the gas supply. Kraemer et al 14 have reported on the dangers posed by these fireplaces to adults who are refueling them. These too have glass doors that might cause a similar problem.…”
Section: Discussionmentioning
confidence: 98%
“…Recently, bioethanol-design fireplaces have been gaining in popularity because they do not need to be connected to the gas supply. Kraemer et al 14 have reported on the dangers posed by these fireplaces to adults who are refueling them. These too have glass doors that might cause a similar problem.…”
Section: Discussionmentioning
confidence: 98%
“…Several researchers have reported on skin burns as a result of accidents involving biofuel heaters [ 22 , 23 , 24 , 25 , 26 , 27 ]. During the literature study, some similar incidents were also found at educational demonstrations [ 29 , 30 ] and in dentist office treatments [ 28 ].…”
Section: Analysis Of Selected Cases Described In the Literaturementioning
confidence: 99%
“…The study by Kraemer et al [ 22 ] presents two cases of patients presented to their intensive care unit in Germany succeeding burns related to bioethanol fuel. The first patient was a 45-year-old female with 30% total body surface area (TBSA) deep partial- and full-thickness flame burns involving the face, neck, right chest, thighs, and both arms and hands.…”
Section: Analysis Of Selected Cases Described In the Literaturementioning
confidence: 99%
See 2 more Smart Citations